Practice of License to Open State Land in Balikpapan - Deasy Ratna Sari (Unram Law Review, 2017)
This study aims to find out why the License to Open State Land can be the basis for land registration and to know the legal consequences on the sale and purchase of land objects based on the License to Open State Land. This research is done empirically juridically, that is by collecting data by researching and examining facts that exist in line with the observation in the field. Land issues in Indonesia are the responsibility of all parties involved, including the responsibilities of the central and local governments. The Local Government of Balikpapan City stipulates the IMTN regulation. The result of this research is the regional regulation aims to prevent and reduce the existence of land disputes by the orderly administration of land affairs. Land Acquisition License Can Become the Foundation for Land Land Registration because it is legally determined that the license holder can apply for a right to land within 3 years since the IMTN is issued. As a result of the Law on Sale and Purchase of Land Objects Based on the License to Open the Land of the State ie the agreement becomes null and void and the sale and purchase agreement is considered never existed.